Implemention of perfectly matched layer absorbing boundary condition for CN‐RPIM method. Issue 6 (1st March 2017) - Zhu, Hui; Gao, Cheng; Chen, Hailin; Yin, Qin
Abstract : In this Letter, the perfectly matched layer (PML) absorbing boundary condition is incorporated into the unconditionally stable radial point interpolation meshless method based on Crank–Nicolson radial point interpolation method scheme. By splitting field variables in the whole computational domain, all variables are defined in the support domain of nodes near PML boundary, and an implicit time‐stepping formulation is derived. Numerical experiment is implemented to demonstrate the performance of the implemented PML.